Handbook of Positive Youth Development: Advancing Research, Policy, and Practice in Global Contexts (Review) - Manrique Millones, Denisse Lisette (2021)
Reseña del libro Handbook of Positive Youth Development: Advancing Research, Policy, and Practice in Global Contexts. Radosveta Dimitrova and Nora Wiium (Eds.) (Cham: Springer), 2021, 754 pages, ISBN 978-3-030-70261-8